THE IMPLEMENTATION OF COOPERATIVE PRINCIPLE IN “UP” MOVIE: PRAGMATIC APPROACH - Bagus Wahyu Utomo; Ambalegin, Ambalegin (eScience Humanity Journal, 2023)
This research was about cooperative principle in Up movie. The purposes of this research were to find out and explain the types of maxims in Up movie. This movie showed the conversation between the senior citizen and a kid who had different level the way of thinking. Their ideas while speaking gave experience how people with different level of age avoid misunderstanding. By looking at the connection between questions and answers or responses showed the cooperative conversation. This research applied the theory of cooperative principle with four maxims theorized by Grice. This descriptive qualitative research used the observational method to collect the data and pragmatic identity method to analyze the data. The result of this analysis was the maxim of quantity, maxim of quality, maxim of relevant, and maxims of manner applied by the characters. It showed that the different age of the speakers will not change the meaning of each speaker because the speakers have the same perception and aim. Additionally, the maxim of manner is the most used data and the maxim of quality was the least data used in Up movie.